Model Pendidikan Kesehatan Mental Berbasis Komunitas bagi Remaja di Kota Mataram - Yulianti Susila Putri; Heri Santoso; Nuarasiah Jamil (UNITY: Journal of Community Service, 2026)
Adolescent mental health problems show an increasing trend in urban areas, including Mataram City. Limited mental health literacy and weak community involvement reduce the effectiveness of early prevention efforts. This article aims to examine the implementation of a community-based mental health education model for adolescents within a community service program. The program applied a participatory approach through group education, psychoeducation, and strengthening adolescent peer facilitators. Activities were conducted in selected urban communities in Mataram City involving adolescents aged 13 to 18 years, parents, and community leaders. Program evaluation used pre- and post-intervention measurements of knowledge, attitudes, and coping skills related to mental health. The results indicate a significant increase in mental health knowledge scores and more positive attitudes toward psychological help-seeking behavior. Active adolescent participation also improved after the community-based intervention. This model demonstrates practical value as a promotive and preventive strategy for adolescent mental health at the local level. The findings support the integration of community-based approaches into urban adolescent mental health programs.